Comparative health risk assessment of in-vehicle exposure to formaldehyde and acetaldehyde for taxi drivers and passengers: Effects of zone, fuel, refueling, vehicle's age and model. (November 2019) - Hadei, Mostafa; Shahsavani, Abbas; Hopke, Philip K.; Kermani, Majid; Yarahmadi, Maryam; Mahmoudi, Babak
Abstract: This study aimed to assess the carcinogenic and non-carcinogenic risks of in-vehicle exposure in Tehran, Iran to formaldehyde and acetaldehyde for different models of taxis, and to explore the effects of city zone, taxi vehicle type, the taxi's age (<1, 1–5, 5–10), fuel type (gasoline, CNG, and LPG), and refueling activities on the estimated health risks based on previously measured concentrations. The overall and age-specific carcinogenic and non-carcinogenic risks of these compounds for taxi drivers and passengers were estimated separately using Monte Carlo simulations. Three scenarios of exposure frequency were defined for taxis commuting in different zones of city: Restricted Traffic Zone (RTZ) and Odd-Even Zone (OEZ) as two plans to reduce air pollution, and no-restriction zone (NRZ). The carcinogenic risks for drivers and passengers, the average risks of formaldehyde and acetaldehyde for most cases were above the 1 × 10 −4 . The health risks were greater in Restricted Traffic Zone (RTZ) and Odd-Even Zone (OEZ) in comparison to no-restriction zone (NRZ). The carcinogenic risk from formaldehyde exposures were higher than those for acetaldehyde in all cases. Taxis fueled with LPG showed lower cancer risks for both acetaldehyde and formaldehyde. Refueling increased the carcinogenic risk from both compounds. For non-carcinogenic risks from acetaldehyde, the average hazard ratios for both drivers and passengers were >1, indicating a non-negligible risk. Cancer and non-cancer risks for the taxi drivers were greater than the passengers given the higher time of occupancy. The present study showed that transportation in taxis can impose significant long-term health risks to both passengers and drivers. Development and investment in cleaner choices for public transportations are required. Graphical abstract: Image 1 Highlights: Many health risks for drivers and passengers were above protective limits. The risks from formaldehyde exposures were higher than those for acetaldehyde. The risks in zones designed for air pollution control were higher than other areas. Cancer and non-cancer risks for the taxi drivers were greater than the passengers. Abstract : This study investigates the cancer and non-cancer risks of two hazardous pollutants inside the cabins of taxis.